HUBUNGAN FAKTOR INDIVIDU DAN PEKERJAAN TERHADAP KELELAHAN PEKERJA KEDAI KOPI DI KECAMATAN DENPASAR BARAT - Putri, Alifa Anisa; Saputra, Adi (ARCHIVE OF COMMUNITY HEALTH, 2025)
Occupational fatigue is a condition where the body becomes weak physically and motivationally. Fatigue conditions can be influenced by various factors, such as individual and occupational factors. Apart from being considered a basic need, food and beverages are now also a trend that must be followed. The emergence of the coffee shop trend has increased job opportunities in this field. This study aims to determine the relationship between the factors that influence the incidence of occupational fatigue in coffee shop workers in terms of individual characteristics and occupational factors. This study is a quantitative study with a cross-sectional design. The research sample is 66 coffee shop workers. Data analysis performed included univariate and bivariate analysis with simple logistic regression tests. The results of the analysis show that the individual factor associated with coffee shop workers fatigue in West Denpasar District is gender (OR=6,5; 95% CI=1,85-22,7; p=0,003). Meanwhile, there are no work factors related to the fatigue of coffee shop workers in West Denpasar District. It is recommended that coffee shop workers pay attention to nutritional intake and stretch in between jobs to reduce the risk of work fatigue. Keywords: occupational fatigue, coffee shop workers, individual factors, occupational factors